Azalea Lace Bug, Stephanitis pyrioides (Scott) (Insecta: Hemiptera: Tingidae) - Jamba Gyeltshen; Amanda Hodges (EDIS, 2006)
EENY-373, a 5-page illustrated fact sheet by Jamba Gyeltshen and Amanda Hodges, describes this pest of ornamental trees and shrubs. Part of the Featured Creatures series, this publication covers the distribution, description, life history, host plant, damage, management, and selected references. Published by the UF Department of Entomology and Nematology, May 2006.